African Wild Dog Dispersal and Implications for Management. Issue 4 (21st February 2020) - Cozzi, Gabriele; Behr, Dominik M.; Webster, Hugh S.; Claase, Megan; Bryce, Caleb M.; Modise, Boitshepho; Mcnutt, John W.; Ozgul, Arpat
ABSTRACT: Successful conservation of species that roam and disperse over large areas requires detailed understanding of their movement patterns and connectivity between subpopulations. But empirical information on movement, space use, and connectivity is lacking for many species, and data acquisition is often hindered when study animals cross international borders. The African wild dog ( Lycaon pictus ) exemplifies such species that require vast undisturbed areas to support viable, self‐sustaining populations. To study wild dog dispersal and investigate potential barriers to movements and causes of mortality during dispersal, between 2016 and 2019 we followed the fate of 16 dispersing coalitions (i.e., same‐sex group of ≥1 dispersing African wild dogs) in northern Botswana through global positioning system (GPS)‐satellite telemetry. Dispersing wild dogs covered ≤54 km in 24 hours and traveled 150 km to Namibia and 360 km to Zimbabwe within 10 days. Wild dogs were little hindered in their movements by natural landscape features, whereas medium to densely human‐populated landscapes represented obstacles to dispersal. Human‐caused mortality was responsible for >90% of the recorded deaths. Our results suggest that a holistic approach to the management and conservation of highly mobile species is necessary to develop effective research and evidence‐based conservation programs across transfrontier protected areas, including the need for coordinated research efforts through collaboration between national and international conservation authorities. © 2020 The Wildlife Society. Abstract : Our analysis of dispersal data on African wild dogs collected across the Kavango‐Zambesi Transfrontier Conservation Area revealed transboundary movements, and human presence and activities as main barriers to dispersal and causes of mortality. This study highlights how the conservation of highly mobile species such as the African wild dog necessitates a holistic approach that incentivizes protection outside protected areas and across wider human‐dominated landscapes and international boundaries.